Effect of ertugliflozin on renal function and cardiovascular outcomes in patients with type 2 diabetes mellitus: A systematic review and meta-analysis. Issue 10 (10th March 2023) - Cheng, Qian; Zou, Shupeng; Feng, Chengyang; Xu, Chan; Zhao, Yazheng; Shi, Xuan; Sun, Minghui
Abstract : Background: The global prevalence of type 2 diabetes mellitus (T2DM) is growing yearly. The efficacy of ertugliflozin (ERT), a recently licensed anti-diabetic drug, has been widely reported. However, additional evidence-based data is required to ensure its safety. In particular, convincing evidence on the effects of ERT on renal function and cardiovascular outcomes is needed. Methods: We searched PubMed, Cochrane Library, Embase, and Web of Science for randomized placebo-controlled trials of ERT for T2DM published up to August 11, 2022. Cardiovascular events here mainly refer to acute myocardial infarction and angina pectoris (AP) (including stable AP and unstable AP). The estimated glomerular filtration rate (eGFR) was used to measure renal function. The pooled results are risk ratios (RRs) and 95% confidence intervals (CIs). Two participants worked independently to extract data. Results: We searched 1516 documents and filtered the titles, abstracts, and full text, 45 papers were left. Seven trials met the inclusion criteria and were ultimately included in the meta-analysis. The meta-analysis found that ERT reduced eGFR by 0.60 mL·min −1 ·1.733 m −2 (95% CI: −1.02–−0.17, P = .006) in patients with T2DM when used for no more than 52 weeks and these differences were statistically significant. Compared with placebo, ERT did not increase the risk of acute myocardial infarction (RR 1.00, 95% CI: 0.83–1.20, P = .333) and AP (RR 0.85, 95% CI: 0.69–1.05, P = .497). However, the fact that these differences were not statistically significant. Conclusion: This meta-analysis shows that ERT reduces eGFR over time in people with T2DM but is safe in the incidence of specific cardiovascular events.